Fission track and U–Pb double dating of detrital zircon applied to the intracratonic Mesozoic Bauru Basin, Brazil. (15th October 2017) - Dias, A.N.C.; Chemale, F.; Hackspacher, P.C.; Soares, C.J.; O‐Aristizabal, C.I.; Tello, C.A.S.
Abstract : Coupled fission‐track and U–Pb analyses of detrital zircons are presented. A Cretaceous intracratonic basin formed between 93 to 60 Ma, the Bauru Basin, is investigated to distinguish its provenance and information about the main orogenetic events of the South American Platform. The results of U–Pb zircon dating suggest that Rhyacian (Transamazonian Cycle, 2.3–2.05 Ga), Statherian (1.8–1 Ga), Sunsás (1.2–0.9 Ga), Tonian (Early Brasiliano, 1 to 0.85 Ga) and Brasiliano (0.65 to 0.50 Ga) terranes and units are the main source areas. The fission‐track data provide important evidence of cooling during the Early Brasiliano and Brasiliano periods and yields 2 main Paleozoic age populations, one between 500 and 360 Ma and the other between 345 and 230 Ma. These populations were interpreted as resulting from different tectonic events along the western margin of the South American Platform that affected the platform's internal composition by uplift and exhumation.